Pharmacognostic, physiochemical and Phytochemical Profile of Alpinia galanga (L.) Willd. and Alpinia calcarata Roscoe - Mathew, Silvy (International Journal of Scientific Research in Biological Sciences, 2018)
Alpinia galanga and Alpinia calcarata (Zingiberaceae), are rare, fast disappearing, threatened species and well known ayurvedic herbs and are used as medicine due to anti-bronchitis, anti-inflammatory, anti-cancerous, anti-cough, anti-diabetic and anti-bacterial properties. The aim of present study was to gather information for the systematic identification and authentication of these valuable species as per WHO guidelines. Powdered leaves of A.calcarata showed high alcohol soluble extractive value, high moisture content, total ash value than rhizome powder and contrary in A.galanga. On the basis of fluorescence analysis rhizomes of these species carry more active ingredients chiefly used for therapeutical purposes. The presences of alkaloids, steroids, flavonoids etc. were confirmed during preliminary phytochemical screening. The pharmacognostic characters obtained in the present investigation might be useful in drug industry for the identification, authentication and quality of commercial samples supplied by suppliers and will be very useful in designing the monograph on these drugs in the Indian Pharmacopoeia.